The effect of the glucosylceramide synthase inhibitor lucerastat on cardiac repolarization: results from a thorough QT study in healthy subjects - Markus S. Mueller (Orphanet Journal of Rare Diseases, 2020)
Abstract Background Fabry disease is a rare inherited glycosphingolipid storage disorder caused by deleterious mutations in the GLA gene coding for the lysosomal enzyme α-galactosidase A. The glucosylceramide synthase inhibitor lucerastat is an iminosugar with potential to provide oral substrate reduction therapy in Fabry disease, regardless of the patient´s underlying mutation. Since lucerastat exhibits systemic exposure and many patients with Fabry disease suffer from rhythm and conduction abnormalities its effects on cardiac repolarization were evaluated in a thorough QT study. Methods In Part A of this randomized, double-blind, placebo-controlled phase 1 study, single oral doses of 2000 and 4000 mg lucerastat were investigated to determine the supratherapeutic dose for Part B. The latter was a four-way crossover study to demonstrate that lucerastat at single oral therapeutic and supratherapeutic doses had no effect on the QTc interval > 10 ms using concentration-QTc modeling as primary analysis. The primary ECG endpoint was placebo-corrected change-from-baseline (ΔΔ) in Fridericia-corrected QTc (ΔΔQTcF). Open-label moxifloxacin served as positive control. Results The effect of lucerastat on ΔΔQTcF was predicted as 0.39 ms (90% confidence interval [CI] − 0.13 to 0.90) and 1.69 ms (90% CI 0.33–3.05) at lucerastat peak plasma concentration after dosing with 1000 mg (5.2 µg/mL) and 4000 mg (24.3 µg/mL), respectively. A QTcF effect > 10 ms was excluded up to lucerastat plasma concentrations of approximately 34.0 µg/mL. Lucerastat did not exert an effect on other ECG parameters. Across doses, absorption of lucerastat was rapid, its elimination half-life ranged from 8.0 to 10.0 h, and the pharmacokinetics (PK) of lucerastat were dose-proportional. Moxifloxacin PK were in line with published data and assay sensitivity was demonstrated by the moxifloxacin QTc response. Lucerastat was safe and well tolerated. Conclusions Lucerastat up to a dose of 4000 mg has no clinically relevant liability to prolong the QT interval or any clinically relevant effect on other ECG parameters. This will be an important factor in the overall benefit-risk assessment of lucerastat in the potential treatment of Fabry disease. Trial registration The study was registered with the ClinicalTrials.gov identifier NCT03832452 (February 6th, 2019, https://clinicaltrials.gov/ct2/show/NCT03832452 ) and the EudraCT number 2018-004546-42 (December 17th, 2018).